Population ecology of small rodents and marsupials in a semi-deciduous tropical forest of the southeast Pantanal, Brazil - Cecilia S. de Andreazzi; Vitor Rademaker; Rosana Gentile; Heitor M. Herrera; Ana M. Jansen; Paulo S. D'Andrea (Zoologia (Curitiba), 2011)
The Pantanal is a South American biome characterized by extensive plains and stark environmental seasonality. Several habitats are subject to annual flooding, forcing small mammal species to aggregate in dry forest patches, which most likely influences their population dynamics and life history strategies. In order to investigate the seasonal influence on the life history traits of these small mammals, we conducted a 2-year mark-recapture study in the southeastern region of the Brazilian Pantanal (Nhecolândia) and analyzed the population dynamics of the most abundant small mammal species with the jackknife estimator. A trapping effort of 21,560 trap-nights resulted in 615 individuals in 1,171 captures (success = 5.43%). Three species of rodents - Oecomys mamorae (Thomas, 1906), Thrichomys pachyurus (Wagner, 1845), and Clyomys laticeps (Thomas, 1841) - and three species of marsupials - Gracilinanus agilis (Burmeister, 1854), Thylamys macrurus (Olfers, 1818), and Monodelphis domestica (Wagner, 1842) - were obtained. The most abundant species was O. mamorae, followed by G. agilis and T. pachyurus. Oecomys mamorae was more abundant in the wet season and presented an opportunistic reproductive strategy. Gracilianus agilis displayed increased population sizes in the dry season and synchronized, seasonal reproduction during the rainy season. Thrichomys pachyurus had a small population size, delayed response to variations in environmental conditions and higher reproductive rates in the dry season. All species revealed different life history strategies (seasonal, opportunistic or delayed response to environmental variations), coinciding with periods of higher resource availability in order to maximize survival.